The Spiritual and Mystical Works of Teresa of Avila in 19th-Century Slovenia - Bošnjak, Blanka (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
This article presents the spiritual and mystical work of a highly influential 16th-cen-tury Spanish author known by her religious name, Teresa of Jesus (Teresa de Jesús), also referred to as Teresa of Ávila after her birthplace. Her first independently published work in Slovenia in the 19th century was a spiritual autobiography with mystical elements, adapted by the German author Simon Buchfelner and trans-lated into Slovene by Jožef Burger in 1834, titled Svete Terezije premišljevanja in perserčni pogovori z’ Bogam, z’ njenim popisam svoje mladosti in z nekterimi njenimi uki (St. Teresa’s Meditations and Intimate Conversations with God, with her account of her youth and some of her teachings (1834)).